Planning for decentralized, simplified prEP: Learnings from potential end users in Ga-Rankuwa, gauteng, South Africa - Mataboge, Paballo; Nzenze, Susan; Mthimkhulu, Nqaba; Mazibuko, Mbali; Kutywayo, Alison; Butler, Vusile; Naidoo, Nicolette; Mullick, Saiqa (Frontiers in Reproductive Health, 2023)
Background: In South Africa, youth experience challenges with oral Pre-Exposure Prophylaxis (PrEP) access and uptake. Taking services out of healthcare settings has the potential to increase reach and overcome these challenges. This paper presents young and older people’s preferences for decentralized, simplified PrEP service delivery and new long-acting HIV prevention methods, in Ga-Rankuwa, South Africa. Methods: Between May and August 2021, both PrEP user and non-user adolescent girls and young women (AGYW), pregnant AGYW, female sex workers, adolescent boys and young men (ABYM), and men who have sex with men (MSM) were recruited to participate in focus group discussions (FDGs) in Ga-Rankuwa, Gauteng. Twenty-two FGDs were conducted. Participants were asked about PrEP uptake, potential acceptability of long-acting HIV prevention products, provision of integrated, simplified, and decentralized services, and digital tools to facilitate access to PrEP and other SRH services. A qualitative approach using inductive thematic analysis was carried out to explore emerging themes on decentralized, simplified delivery and the acceptability of long-acting methods. Results: Of the 109 participants included in the study approximately 45% (n=50) were female, the median age was 23 years ± 5.3. A third (n=37) were current or previous PrEP users, of which, 59.5% (n=22) collected PrEP refills from the clinic. Decentralized, simplified service delivery was appealing; health facilities, pharmacies and institutions of learning were preferred as service points for PrEP and SRH services, and recreational spaces preferred for dissemination of health information and engagement. ABYM were more open to having recreational spaces as service points. Long-acting Cabotegravir was preferred over the Dapivirine Vaginal Ring due to concerns around perceived side-effects, efficacy, and comfort. Conclusion: Providing long-acting PrEP methods through decentralized, simplified service delivery was appealing to this population. They provided practical locations for decentralized service provision to potentially increase their engagement with and uptake of HIV prevention and SRH services.